KHẢO SÁT MỘT SỐ ĐẶC ĐIỂM BỆNH LÝ LÂM SÀNG VÀ HIỆU QUẢ ĐIỀU TRỊ NGOẠI KHOA BỆNH KHỐI U TRUYỀN QUA ĐƯỜNG SINH DỤC Ở CHÓ ĐƯỢC NUÔI TẠI THÀNH PHỐ HUẾ - Hải, Vũ Văn; Tuân, Hà Minh; Tuyến, Nguyễn Thị Kim (Tạp chí điện tử Khoa học và công nghệ nông nghiệp, 2020)
Nghiên cứu này nhằm tìm hiểu một số đặc điểm và đánh giá hiệu quả điều trị bệnh khối u truyền qua giao phối (CTVT) ở chó. Nghiên cứu được thực hiện trên 12 chó có dấu hiệu mắc bệnh được người dân yêu cầu khám và chữa trị. Kết quả cho thấy bằng kỹ thuật mô bệnh học phát hiện thấy khối u có nhiều “cành” được cấu tạo từ mô liên kết. Tế bào khối u có các hạt xếp sát phía trong của màng tế bào. Quan sát đại thể cho thấy khối u có kích thước 6,6 x 4,5 cm (ở con đực) và 6,9 x 5,5 cm (ở con cái). Sau phẫu thuật 6 tháng, 100% chó cái và 80% chó đực thí nghiệm sống khỏe mạnh và không phát hiện thấy khối u tái phát. Tuy nhiên, 1 trường hợp chó đực được phát hiện CTVT tái phát. Đây là những kết quả mới về bệnh CTVT chưa từng được công bố tại Việt Nam. Kết luận, chó bị bệnh CTVT có thể được chẩn đoán thông qua khám lâm sàng, chẩn đoán xác định bằng mô bệnh học, và điều trị bệnh CTVT bằng phẫu thuật mang lại khả năng thành công cao. Từ khóa: Chó, Khối u truyền qua giao phối, Mô bệnh học, Phẫu thuật CLINICAL AND PATHOLOGICAL STUDIES AND THE EFECT OF SURGICAL TREATMENT ON THE CANINE TRANSMISIBLE VENERAL TUMOR IN DOGS (CTVT) IN HUE CITY ABSTRACT This study aimed to diagnose, describe some characteristics and evaluate the effectiveness of surgical treatment method in dogs being suffered from Canine Transmisible Veneral Tumor (CTVT). The study was conducted on 12 dogs (7 females and 5 males) showing signs of disease that people requested for examination and treatment. The results showed that dog breeds, including German shepherd, Vietnamese native breeds, poodles, and crossbreeds at the age of 3-4, have direct mating activities; including males and females have possibility to be infected. Histopathological study found that the tumor was shaped like a cauliflower, with roots attached to the walls of the reproductive organs of infected dogs. Inside the tumor, there are many "branches" made of connective tissue. Tumor cells are characterized by a relatively large size, with granules lining inside the cell membrane. Gross observations showed that the tumor is normally about 6.6 x 4.5 cm (in males) or 6.9 x 5.5 cm (in females), which is formed nearafter the bulbus glandis in males, and at the vulva wall in female reproductive organ. Using surgical methods to remove the tumor showed that 100% female dogs and 80% male dogs were healthy living and no tumor recurrence was detected after 6 months of follow-up post-surgery. However, a male dog was detected to relapse with CTVT. This is the first time that our results of CTVT have been reported in Vietnam. In conclusion, dogs infected by CTVT can be diagnosed through clinical examination, confirmed by histopathological diagnosis. Treating CTVT with surgery brings a high probability of success. Keywords: Dogs, Histopathology, Surgery, Tumors transmitted through mating in dog